EFFECT OF GINGER EXTRACT (ZINGIBER OFFICINALE) AS A NATURAL ANTIOXIDANT ON SUNFLOWER OIL OXIDATION - Elsorady, Muhammad Elsayed; Elgindy, Asma (Food and Feed Research, 2022)
Oil oxidation is significant for acceptability, nutritional quality, and toxicity of edible oils. Antioxidant supplementation for oil is a common and fundamental strategy for improving its oxidative stability and prolonging induction time. Ginger contains natural antioxidants such as phenolic and flavonoid compounds. Ginger extracts were prepared by extraction with different solvents (methanol, ethanol, acetone and water). Ethanolic ginger extract had the highest yield (10.52%), whereas the aqueous extract had the lowest yield (8.10%). Also, the ethanolic extract was the highest in the content of phenolic and flavonoid compounds (75.17 and 19.55 mg/g, respectively), followed by methanolic extract (67.24 and 17.46 mg/g, respectively). Thus, further elaboration focused on the ethanolic extract. The scavenging ability of ginger extract was dose-dependent; it increased with the increase in ginger extract concentration. As expected, the ginger extract had lower DPPH scavenging activity than BHT (synthetic antioxidant). Free fatty acid (FFA), peroxide value (PV), conjugated dienes (CD) and thiobarbituric acid (TBA) value were used to evaluate the effect of ginger extract as a natural antioxidant on sunflower oil oxidation. The higher the concentration of ginger extract, the lower the magnitude of FFA, PV, CD, and TBA in sunflower oil. According to our findings, the level of sunflower oil supplementation with ginger extract should be below 600 mg/kg. The result of this study suggests that ginger extract can be recommended as a natural antioxidant to retard sunflower oil oxidation.
Keywords: flavonoids; phenolics; scavenging activity; solvents; storage; oxidative stability